The Effect of Training Circuit Exercise on the Resistance of Badminton Game for the Atlet Club of Rtv Pekanbaru - Slamet, Slamet; Sulastio, Agus; Wiranata, Agus (Proceedings of the UR International Conference on Educational Sciences, 2018)
Based on observations that the author has done at the Pekanbaru RTV Club during training and the match, the author sees and encounters several problems, namely: tiredness of the athlete in doing the exercises and matches so that the exercise is not maximal, the athlete not freely in moves and moves to another place due to excessive fatigue so that the movement is not maximal. The purpose of this study is to see the effect of training on endurance Badminton athletes at RTV Pekanbaru club. In this study, researchers took a population of 8 people. The sample in this study uses a total sampling technique, where all populations are sampled. Subsequently, the data obtained from the bleep test, and then, the data were analyzed using the t-test. Based on the research conducted on 8 samples by conducting a pre-test (initial test) bleep test. Then proceed with treatment (Circuit training) for 16 meetings, after which a bleep test was conducted, the results obtained from the pretest and posttest were analyzed by t-test based on the t-test analysis yielded tcount of 2.595 with t table 1.753 then Ha was received, at an alpha level (Î±) 0.05. It can be concluded that there is an effect of training circuit training on endurance Badminton athletes at RTV Pekanbaru club athletes.